Antimicrobial photodynamic therapy using a diode laser with a potential new photosensitizer, indocyanine green‐loaded nanospheres, may be effective for the clearance of Porphyromonas gingivalis. (14th January 2013) - Nagahara, A.; Mitani, A.; Fukuda, M.; Yamamoto, H.; Tahara, K.; Morita, I.; Ting, C.‐C.; Watanabe, T.; Fujimura, T.; Osawa, K.; Sato, S.; Takahashi, S.; et al.
Abstract : Background: Antimicrobial photodynamic therapy (aPDT) is a new treatment method for the removal of infectious pathogens using a photosensitizer and light of a specific wavelength, e.g., toluidine blue with a wavelength of about 600 nm. We explored a new photosensitizer and focused on indocyanine green (ICG), which has high absorption at a wavelength of 800–805 nm. We investigated the bactericidal effect of PDT on Porphyromonas gingivalis using a new photosensitizer, ICG‐loaded nanospheres with an 805 nm wavelength low‐level diode laser irradiation. Methods: We designed ICG‐loaded nanospheres coated with chitosan (ICG‐Nano/c) as a photosensitizer. A solution containing Porphyromonas gingivalis (10 8  CFU/mL) with or without ICG‐Nano/c (or ICG) was prepared and irradiated with a diode laser or without laser irradiation as a negative control. The irradiation settings were 0.5 W with a duty ratio of 10%, for 3–100 ms in repeated pulse (RPT) or continuous wave mode. CFU were counted after 7 d of anaerobic culture. Results: We observed that ICG‐Nano/c could adhere to the surface of P. gingivalis . When ICG‐Nano/c was used for aPDT, irradiation with RPT 100 ms mode gave the lowest increase in temperature. Laser irradiation with ICG‐Nano/c significantly reduced the number of P. gingivalis (i.e., approximately 2‐log10 bacterial killing). The greatest bactericidal effect was found in the RPT 100 ms group. However, laser irradiation (RPT 100 ms) with ICG, as well as without photosensitizer, had no effect on the number of bacteria. Conclusions: Within the limits of this study, ICG‐Nano/c with low‐level diode laser (0.5 W; 805 nm) irradiation showed an aPDT‐like effect, which might be useful for a potential photodynamic periodontal therapy.